The Influence of Social Media Influencers, Tourist Attractions, and Social Media Marketing on Travel Decisions with Visiting Intention as an Intervening Variable - Anindya; Lilik Wahyudi (LP2M IAIN Palopo, 2026)
Solo, or better known as Surakarta, is one of the cities rich in history and culture in Indonesia. This city is not only home to various cultural heritages, but also an attractive tourist destination for domestic and international tourists. The purpose of this study is to determine the influence of social media influencers, tourist attractions, and social media marketing on tourist visit decisions, with interest in visiting as an intervening variable. The research method used is quantitative with SMARTPLS software. The results of the study concluded that there is a significant positive influence of social media influencers on visit decisions. There is no influence between tourist attractions and visit decisions. There is an influence between social media marketing and visit decisions. There is no influence between interest in visiting and visit decisions. Interest in visiting cannot mediate the relationship between social media influencers and visit decisions. Also, interest in visiting cannot mediate the relationship between tourist attractions and visit decisions, and interest in visiting cannot mediate the relationship between social media marketing and visit decisions.